2018
DOI: 10.3389/fpls.2018.00667
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Formation of Methylglyoxal-Derived Advanced Glycation End Products in Arabidopsis Under Ammonium Nutrition

Abstract: Nitrate (NO3–) and ammonium (NH4+) are prevalent nitrogen (N) sources for plants. Although NH4+ should be the preferred form of N from the energetic point of view, ammonium nutrition often exhibits adverse effects on plant physiological functions and induces an important growth-limiting stress referred as ammonium syndrome. The effective incorporation of NH4+ into amino acid structures requires high activity of the mitochondrial tricarboxylic acid cycle and the glycolytic pathway. An unavoidable consequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 92 publications
3
43
0
Order By: Relevance
“…As mentioned above, based on our own observations [67] and the data obtained by other groups [61,107], the main glycation pathways in plants are mediated by α-dicarbonyls. Although the most abundant plant α-dicarbonyl is GO, MGO is much better studied in terms of its formation, reactivity and biological role in plants.…”
Section: Possible Role Of Protein Glycation In Plant Physiologymentioning
confidence: 84%
“…As mentioned above, based on our own observations [67] and the data obtained by other groups [61,107], the main glycation pathways in plants are mediated by α-dicarbonyls. Although the most abundant plant α-dicarbonyl is GO, MGO is much better studied in terms of its formation, reactivity and biological role in plants.…”
Section: Possible Role Of Protein Glycation In Plant Physiologymentioning
confidence: 84%
“…3P4 and 4P11, has revealed an increase in GLYI and GLYII activities in the plants subjected to both N-deficient and N-excess conditions, especially in the case, where ammonium was used as a N source [58]. In a similar context, the impact of MG in contributing towards NH 4 + toxicity symptoms in Arabidopsis has been recently studied [59]. Since effective incorporation of ammonium ions into the amino acid structures entails high activity of mitochondrial TCA and engagement of the glycolytic pathway, generation of MG is unavoidable under such circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The glycolytic metabolism produces methylglyoxal (MG) as a toxic by-product, which severely inhibits cell growth in plants. The MG content steeply increases during abiotic stresses and is required to be neutralized in order to maintain the cellular physiology [73]. Banu et al [74] reported the exogenous application of GB to decrease the MG and H2O2 content in tobacco cells cultured in a saline medium.…”
Section: Glycinebetaine-induced Antioxidant Defensementioning
confidence: 99%